Strength of Constitutional Court Decisions in Judicial Review of the 1945 Constitution in Indonesia: Kekuatan Putusan Mahkamah Konstitusi dalam Pengujian Undang-Undang terhadap Undang-Undang Dasar 1945 di Indonesia - Mexsasai Indra; Geofani Milthree Saragih; Mohamad Hidayat Muhtar (Jurnal Konstitusi, 2023)
This research discusses the strength of the Constitutional Court's decision regarding judicial review in Indonesia. The Constitutional Court is an institution of judicial power tasked with exercising the authority of judicial review born from the 3rd Amendment to the 1945 Constitution. In this study, the philosophical and normative foundations that form the basis for the strength of the Constitutional Court's decision to conduct judicial review will be discussed. The method used is normative juridical, using secondary materials such as laws, decisions of the Constitutional Court, and related legal literature. This study's results confirm that the Constitutional Court's decision to conduct a judicial review has a powerful dimension of power. This power can be viewed from several angles, both philosophical and normative. In the philosophical aspect, the strength of the Constitutional Court's decision lies in the principles of popular sovereignty and constitutional supremacy. While in the normative aspect, the strength of the Constitutional Court's decision is based on the provisions of laws and regulations governing the authority and procedures of the Constitutional Court in conducting judicial reviews.